1995
DOI: 10.2514/3.46871
|View full text |Cite
|
Sign up to set email alerts
|

Navier-Stokes computations and experimental comparisons for multielement airfoil configurations

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
1
20
0
2
Order By: Relevance
“…Figure 10 shows the plot of Coefficient of Pressure versus x/c at 16 o angle of attack, comparing results of computational and experimental data of the airfoil MDA30P30N [5]. It can be seen that computed pressure distribution result is in good agreement with the experimental measurements.…”
Section: Numerical Validationsupporting
confidence: 66%
See 1 more Smart Citation
“…Figure 10 shows the plot of Coefficient of Pressure versus x/c at 16 o angle of attack, comparing results of computational and experimental data of the airfoil MDA30P30N [5]. It can be seen that computed pressure distribution result is in good agreement with the experimental measurements.…”
Section: Numerical Validationsupporting
confidence: 66%
“…It was concluded that the S1223RTL airfoil had the most suitable design for the specified boundary conditions and the Mach numbers from 0.10 to 0.30. W. Kyle Anderson et al [5], did an experiment on a twodimensional unstructured Navier-Stokes code utilized for computing the flow around multi-element airfoil configurations. In the experiment, comparisons were shown for a landing configuration with an advanced-technology flap.…”
Section: Literature Surveymentioning
confidence: 99%
“…Similarly, in addition to their direct effect on friction drag, inaccuracies in computed skin friction can alter the prediction of downstream separation locations, which results in a much more profound effect on overall drag prediction. An example of this behavior was originally given Anderson et al, 29 and reproduced in reference, 30 where the effects of inadequate boundarylayer resolution were found to produce premature separation on a two-dimensional high-lift configuration. Examination of individual workshop results has shown that grid resolution requirements for drag prediction involving regions of separated flow are much more demanding and less well understood than for cases where the flow is fully attached.…”
Section: A Grid Resolutionmentioning
confidence: 99%
“…Flow phenomena around high-lift devices are considered challenging for numerical methods and turbulence model discretisation; deployed slat and flap at high angles of attack in combination with low speed, potential unsteady flow regime, flow separation, laminar/turbulent transition, interaction of aerofoil/wing has been previously studied experimentally by Spaid [69]a n db yR u m s e ye ta l [ 70], where 3D effects are analysed including CFD simulations, further CFD work is presented in the following papers [71][72][73][74].…”
Section: Mda 30p-30nmentioning
confidence: 99%